2007
DOI: 10.1108/08858620810841498
|View full text |Cite
|
Sign up to set email alerts
|

Users' adoption of e‐banking services: the Malaysian perspective

Abstract: PurposeThe purpose of this paper is to explore the determinants of users' adoption momentum of e‐banking in Malaysia.Design/methodology/approachA questionnaire with four‐point Likert scale is applied to 324 usable responses. Ten attributes are tested, namely convenience of usage, accessibility, features availability, bank management and image, security, privacy, design, content, speed, and fees and charges.FindingsResults indicate that all elements for ten identified factors are significant with respect to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
292
3
24

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 315 publications
(341 citation statements)
references
References 42 publications
22
292
3
24
Order By: Relevance
“…Thus, other than the personality dimensions, we feel that age of the consumers also plays a signifi cant role in adoption of online banking. 14,17,18 If the sample had various age groups equally represented we believe our results may have been different. There is large representation of younger generation in the sample, which makes it biased.…”
Section: Limitations and Future Researchmentioning
confidence: 86%
See 1 more Smart Citation
“…Thus, other than the personality dimensions, we feel that age of the consumers also plays a signifi cant role in adoption of online banking. 14,17,18 If the sample had various age groups equally represented we believe our results may have been different. There is large representation of younger generation in the sample, which makes it biased.…”
Section: Limitations and Future Researchmentioning
confidence: 86%
“…Research conducted on the adoption of online banking in other developing countries recommends that awareness towards online banking infl uences consumers ' acceptance and use of the services. 15,17,18,44,68 The consumers ' attitude towards online banking is not only governed by environmental issues, but also psychological attributes. The differences in personality of the consumers may motivate or demotivate them to try new services.…”
Section: Management Implicationsmentioning
confidence: 99%
“…Perceived usefulness and perceived ease of use is significant factors affecting acceptance of an information system or new technologies. Prior research has empirically found positive relationship between perceived ease of use and perceived usefulness as critical factors on the use of e-banking [31], [37][38][39]. Hence an application perceived to be useful perceived to be easier to use than another is more likely to be accepted by users.…”
Section: Research Model and Hypothesesmentioning
confidence: 99%
“…Perceived usefulness, security and privacy are the main perusing factors to accept online banking system [20]. According to a study WAP, GPRS and 3G features from mobile devices are of no significance or influence in the adoption of e-banking services [31].…”
Section: Consumer Attitude Towards M-bankingmentioning
confidence: 99%
“…Healy (1999) revealed that long-term customers are less sensitive of the price changes. This was supported by Poon (2007) of which more than 60 percent of the Malaysians are aware of the annual fee, but would continue to use the services.…”
Section: Costmentioning
confidence: 93%